X-men, the last stand [videorecording (Blu-Ray)] - Kinberg, Simon; Penn, Zak, 1968-; Jackman, Hugh; Janssen, Famke, 1964-; Berry, Halle; Grammer, Kelsey, 1955-; McKellen, Ian (20th Century Fox Home Entertainment, 2016)
The mutant heroes sworn to defend a world that hates and fears them are back! With the help of new recruits, they must face evolution itself in the form of a former teammate.